THE OTHER FACE OF ACCOUNTING RESEARCH: A Perspective From Sociological Theory - Mazda Eko Sri Tjahjono (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
Accounting cannot be separated from the social interactions that take place in and around organizations. Accounting research has long been concerned with communication and reporting, negotiations and agreements, interactions with external parties, organizational culture, social and economic impacts, professional roles and ethics. Agency theory has become an inescapable mainstream theory. The purpose of this article is to explain how accounting research uses sociological theory. The research methodology used in this article is a literature review of published articles. The use of sociological theory as an analytical tool to explain contemporary accounting phenomena and practices is very relevant because accounting is part of the social sciences. To maintain the integrity of accounting research with a sociological theoretical approach, it is necessary to establish strict boundaries to ensure that accounting research remains focused on accounting principles and does not deviate from its main objectives. The complexity of the accounting field and the importance of understanding the social context in which financial information is produced, processed and used. This paper is intended to help accounting researchers develop research ideas